(untitled) (American International Journal of Education and Linguistics Research, 2021)
The purpose of this study is to find out the effects of story Reading on improving Reading comprehension and critical thinking of EFL students at Kandahar University. The design of the study was quasi-experimental with reading comprehension and critical thinking pre and Post-tests. Total 27 Afghan EFL students were selected based on their performance on Placement test. The participants’ experimental groups listened to their teacher reading a story aloud. In order to find the improvement and different between these variables is significant the Paired Sample T-Test was administrated and the result indicates that there is significant improvement in post-tests in areas of reading comprehension and critical thinking in story Reading. However, there is more improvement in critical thinking aspect through story reading.